Performance Evaluation of Semitransparent Perovskite Solar Cells for Application in Four-Terminal Tandem Cells - Kirchartz, Thomas; Korgitzsch, Sophie; Hüpkes, Jürgen; Ramírez Quiroz, César Omar; Brabec, Christoph (ACS Energy Letters, 2018)
The efficiency of perovskite-based tandem solar cells and the respective efficiency gain over the single-junction operation of the bottom cell strongly depend on the performance of the component cells. Thus, a fair comparison of reported top cells is difficult. We therefore compute the tandem cell efficiency for the combination of several semitransparent perovskite top solar cells and crystalline silicon or chalcopyrite bottom cells from the literature. We focus on four-terminal configurations but also estimate and discuss the differences between four- and two-terminal configurations. For each top cell, we thereby determine the tandem cell performance as a function of the bottom cell efficiency, which results in a linear relationship. From these data, we extract two parameters to quantify the suitability of the top cell: (i) the slope of the tandem vs. bottom cell efficiency, which is the effective transparency of the top cell, and (ii) the tandem cell efficiency for a targeted bottom cell. These two figures of merit were calculated for a representative set of bottom cells and may serve for comparison of semitransparent perovskite top cells in the future. Copyright © 2018 American Chemical Societ
Keywords: Copper compounds; Efficiency; Perovskite; Perovskite solar cells